A Sociology of Luck. (September 2020) - Sauder, Michael
Sociology has been curiously silent about the concept of luck. The present article argues that this omission is, in fact, an oversight: An explicit and systematic engagement with luck provides a more accurate portrayal of the social world, opens potentially rich veins of empirical and theoretical inquiry, and offers a compelling alternative for challenging dominant meritocratic frames about inequality and the distribution of rewards. This article develops a framework for studying luck, first by proposing a working definition of luck, examining why sociology has ignored luck in the past, and making the case for the value of including luck in sociology's conceptual repertoire. The article then demonstrates the fertile research potential of studying luck by identifying a host of research questions and hypotheses pertaining to the social construction of luck, the real effects of luck, and theoretical interventions related to luck. It concludes by highlighting the distinctive contributions sociology can make to the growing interdisciplinary interest in this topic.